L'interprétation judiciaire de la condition sociale, motif de discrimination prohibé par la Charte des droits du Québec - Brun, Henri; Binette, André (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1981)
The Quebec Charter of Human Rights and Freedoms, L.R.Q.. c. C-12, introduces a new concept among the reasons for which discrimination is forbidden : social condition. Nowhere else in Canada is there given this explicit meaning to the right to equality. Courts appear reluctant to give their proper signification to the words « social condition ». They prefer to rely on the better known expression of « social origin ». The authors of the following comments bel eve that social condition must mean something specific, situated somewhere between social origin and the general right to equality clause.